2009
DOI: 10.1016/j.bcp.2009.01.021
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of cytotoxicity and DNA adduct formation by the anticancer drug ellipticine in human neuroblastoma cells

Abstract: Ellipticine is an antineoplastic agent, whose mode of action is based mainly on DNA intercalation, inhibition of topoisomerase II and formation of covalent DNA adducts mediated by cytochromes P450 and peroxidases. Here, the molecular mechanism of DNA-mediated ellipticine action in human neuroblastoma IMR-32, UKF-NB-3 and UKF-NB-4 cancer cell lines was investigated. Treatment of neuroblastoma cells with ellipticine resulted in apoptosis induction, which was verified by the appearance of DNA fragmentation, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 47 publications
8
81
0
1
Order By: Relevance
“…We found that exposure of human neuroblastoma IMR-32, UKF-NB-3 and UKF-NB-4 cell lines to this agent resulted in strong inhibition of cell growth, followed by induction of apoptosis 7 . These effects were associated with formation of two covalent ellipticine-derived DNA adducts, identical to those formed by the cytochrome P450 (CYP)-and peroxidase-mediated ellipticine metabolites, 13-hydroxy-and 12-hydroxyellipticine (Fig.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…We found that exposure of human neuroblastoma IMR-32, UKF-NB-3 and UKF-NB-4 cell lines to this agent resulted in strong inhibition of cell growth, followed by induction of apoptosis 7 . These effects were associated with formation of two covalent ellipticine-derived DNA adducts, identical to those formed by the cytochrome P450 (CYP)-and peroxidase-mediated ellipticine metabolites, 13-hydroxy-and 12-hydroxyellipticine (Fig.…”
Section: Introductionmentioning
confidence: 87%
“…DNA from cells treated with ellipticine and doxorubicin was isolated by the phenol-chloroform extraction as described 7 .…”
Section: Dna Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity of cell lines to CDDP was determined by using the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) test (22). The IC 50 was assessed using an MTT dye reduction assay as described in a previous report (23). The IC 50 values were calculated from at least 3 independent experiments using linear regression of the dose-log response curves using SoftMax Pro microplate data software (Molecular Devices, Sunnyvale, CA, USA).…”
Section: Methodsmentioning
confidence: 99%